The moon : earth's natural satellite - Branley, Franklyn Mansfield, 1915-2002.; Wimmer, Helmut K. (New York : Crowell, 1960)
Discusses scientific findings about the moon's mass, density, gravity, temperatures, lack of atmosphere, eclipses, orbit, surface, and effect on tides with a section on superstitions.
Keywords: Moon